A development of a framework for evaluation of reverse logistics maturity level. Issue 2 (2018) - Pulansari, Farida; Suparno; Partiwi, Sri Gunani
Reverse logistic (RL) and management of unused product waste, as well as limitation of natural resources, are growing problems throughout the decade. The RL has been successfully implemented in some companies, however, no clear key performance indicator of a successful RL is provided. The paper proposes a framework for assessing the maturity level of the RL implementation. The framework was designed in order to provide the information as well as a clear key performance indicator. The procedure of assessing the framework was to come to many companies to measure the level of RL implementation. Better integration among supply chain actors can minimise the environmental problems. The finding shows that the maturity level in the implementation of RL for the Indonesian consumer electronics industries is at level 3 (develop level) and 2 (managed level), especially in the local companies.